Room-temperature fabrication of Cu nanobrushes as an effective surface-enhanced Raman scattering substrate. Issue 42 (12th October 2016) - Hsu, Yu-Kuei; Chen, Zhong-Bo; Lin, Yu-Chang; Chen, Ying-Chu; Chen, San-Yuan; Lin, Yan-Gu
Abstract : We demonstrated a fabrication method of Cu nanobrushes at room temperature with the application of surface-enhanced Raman scattering. Abstract : A facile route to manufacture an active surface-enhanced Raman-scattering (SERS) substrate based on brush-like Cu nanostructures directly grown on a Cu foil at 23 °C was systematically investigated. A hierarchical Cu nanobrush substrate was fabricated in two cycles of electro-oxidation and chemical reduction in sequence; Cu(OH)2 nanowires (NW) were formed on electro-oxidation, and converted on chemical reduction to Cu NW. Two cycles of this process achieved a brush-like Cu nanostructure; its structure, morphology and composition were examined by XRD, SEM, HRTEM and XPS, respectively. With 4-mercaptobenzoic acid (4-MBA) and chlorothalonil as probe molecules, the SERS experiments showed that the brush-like Cu nanostructures exhibit excellent detection performance, which could serve as effective SERS substrates for ultrasensitive detection. This novel hierarchical SERS substrate shows satisfactory reproducibility and a linear dependence between the analyte concentration and intensity, revealing the advantage of this method for easily scaled production.